The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/iub.2403
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐like protein 4 promotes very‐low‐density lipoprotein assembly and secretion in bovine hepatocytes in vitro

Abstract: In dairy cows, fatty liver is one of the most common metabolic diseases that occurs during the periparturient period. Angiopoietin‐like protein 4 (ANGPTL4) is a well‐known downstream target of peroxisome proliferator‐activated receptors (PPARs), which regulate the glucose and fatty acid metabolisms. The inhibition of lipoprotein lipase (LPL) activity interferes with the storage of triglycerides (TG) in adipocytes, which plays an essential role in lipid metabolism in rodents. However, it remains unclear whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…One study reported that the abundance of angiopoietin-like protein 4 (ANGPTL4) mRNA was increased in all three models of declining EB, suggesting that ANGPTL4 may act as an early autocrine/paracrine or endocrine signal to influence energy status in lactating cattle ( Koltes and Spurlock, 2012 ). Kong et al (2020) reported that ANGPTL4 promotes the transport of triglycerides in the form of very low-density lipoprotein, contributing to the adaptive regulation of the lipid transport system in dairy cattle. Some studies have reported that ANGPTL4 is associated with perinatal fatty liver, ketosis, and other metabolic disorders in dairy cows ( Wang et al, 2018 ; Kong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that the abundance of angiopoietin-like protein 4 (ANGPTL4) mRNA was increased in all three models of declining EB, suggesting that ANGPTL4 may act as an early autocrine/paracrine or endocrine signal to influence energy status in lactating cattle ( Koltes and Spurlock, 2012 ). Kong et al (2020) reported that ANGPTL4 promotes the transport of triglycerides in the form of very low-density lipoprotein, contributing to the adaptive regulation of the lipid transport system in dairy cattle. Some studies have reported that ANGPTL4 is associated with perinatal fatty liver, ketosis, and other metabolic disorders in dairy cows ( Wang et al, 2018 ; Kong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…ApoB, ApoE, MTTP, and LDLR are the main structural and/or regulatory proteins for the assembly and transport of liver VLDL. Their expression promotes the synthesis and secretion of VLDL from the liver and reduces liver fat content [ 22 , 45 , 46 ]. ApoE gene deletion results in the blocked synthesis of TG-rich VLDL and fat accumulation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…After anesthetic treatment using thiamylal sodium, the caudate liver lobe of newborn calves was obtained under aseptic conditions within 24 h. Subsequently, hepatocytes were isolated using a modified 2-step collagenase perfusion method, as described previously [ 19 , 20 ]. Perfusion A (140 mmol/L NaCl, 6.7 mmol/L KCl, 10 mmol/L HEPES, 0.5 mmol/L EDTANa 2 and 2.5 mmol/L glucose; pH 7.2–7.4, 37 °C), perfusion B (140 mmol/L NaCl, 6.7 mmol/L KCl, 30 mmol/L HEPES, 5 mmol/L CaCl 2 , and 2.5 mmol/L glucose; pH 7.2–7.4, 37 °C), and perfusion C (0.2 g/L collagenase IV (Gibco; Gaithersburg, MD, USA) in perfusion B, pH 7.2–7.4, 37 °C) were used [ 21 , 22 ]. After terminating collagenase digestion, the tissue was cut into smaller pieces to release the hepatocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Key lipid synthesis-associated transcripts, which include Fasn and Acc1, did not show any significant changes across the experimental groups. However, the expression of Angptl4, which can promote triglyceride clearance in hepatocytes [21], showed a decrease of over 2-fold in the ETOH-BKO mice compared to the ETOH-WT mice. Meanwhile, the transcript levels of Cyp7A1, a key gene for bile acid synthesis, were increased in the PF-BKO group compared to the PF-WT group.…”
Section: Rarβ Protects Hepatocytes From Alcohol-associated Steatosismentioning
confidence: 92%